Male fertility as a marker for health. Issue 1 (January 2022) - Chen, Tony; Belladelli, Federico; Del Giudice, Francesco; Eisenberg, Michael L.
Abstract: Male reproduction is a complex biological process, and male factor infertility is increasingly recognized as a biomarker for overall male health. Emerging data suggest associations between male reproduction and medical disease (genetic, infectious, chronic comorbid conditions), psychological disease, environmental exposures, dietary habits, medications and substances of abuse, and even socioeconomic factors. There is also evidence that a diagnosis of male fertility is associated with future disease risk including cancer, metabolic disease and mortality. As such, there is a growing view that the male fertility evaluation is an opportunity to improve a man's health beyond his immediate reproductive goals, and also highlights the necessity of a multidisciplinary approach.